URGENSI PENDIDIKAN PERLINDUNGAN HUKUM UNTUK ANAK SEKOLAH - FISKA SIMBOLON, DEWI (Ensiklopedia Education Review, 2019)
The practice of national education is held by referring to certain juridical grounds that have been established, both in the form of laws and government regulations regarding education. Educational goals that educate the life of the nation. Children are the assets of the nation, education is also an asset of the nation but in other terms quality education will bring a nation to progress. As with children, the better the quality of children will bring a nation to progress. This makes education and children two things that are interrelated with each other. Article 28 B paragraph (2) of the 1945 Constitution affirms that: "Every child has the right to survival, to grow and develop and has the right to protection from violence and discrimination", the provision has provided a solid foundation that the child has the right to live, grow and develops and has the right to obtain protection from violence, exploitation and discrimination. Child protection education is all activities to guarantee and protect children and their rights so that they can live, grow and develop, and participate optimally in accordance with human dignity and dignity, and get protection from violence and discrimination. Keywords: Urgency, Education, Child Protection, School.